1990
DOI: 10.1002/ajpa.1330820106
|View full text |Cite
|
Sign up to set email alerts
|

Temporal aspects of biological distance: Serial correlation and trend in a prehistoric skeletal lineage

Abstract: A number of previous studies have examined biological variability within individual human skeletal samples, using internal chronology as an explanatory source for variation. In this paper time series and matrix comparison methods are used to examine temporal serial correlation and trend of biological characteristics within a skeletal sample. These methods follow appropriately upon the assumption that the processes of genetic drift and migration lead to temporal autocorrelation of the mean genotype within indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 30 publications
1
47
0
1
Order By: Relevance
“…Researchers have shown that non-metric trait expression can be attributed to a combination of genetics and environmental influences [15][16][17]. But, no clear consensus is available as to which factor, genetics or environment, is more contributory to the morphological expression of a discrete trait [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have shown that non-metric trait expression can be attributed to a combination of genetics and environmental influences [15][16][17]. But, no clear consensus is available as to which factor, genetics or environment, is more contributory to the morphological expression of a discrete trait [16].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, many researchers are unsure about these traits being valid measures in discerning population differences, particularly among admixed groups such as ''Coloured'' South Africans [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is empirical evidence to suggest a positive relationship between temporal and craniometric distance within certain archaeological sites [47], but the exact parameters of an isolation-by-space and time model are currently unclear. Therefore, we follow the methods described by Pinhasi & von Cramon-Taubadel [3] in applying a model of isolationby-geographical distance, with a correction for temporal autocorrelation, via partial Mantel tests.…”
Section: (D) Analytical Methodsmentioning
confidence: 99%
“…Because the two sides of bilateral traits are invariably correlated (Finnegan 1978), it is necessary to combine the data so that each trait is represented only once when performing biodistance analyses. Two basic methods have been suggested for dealing with bilateral traits and their occasional asymmetry: "side-count methods," which involve adding all sides as independent observations (e.g., Johnson and Lovell 1994;Prowse and Lovell 1996), and "individual count methods," in which each trait is only counted once per individual (e.g., Buikstra 1976;Konigsberg 1990;Korey 1970;McGrath, Cheverud, and Buikstra 1984).…”
Section: Preparing the Data For Population Comparisonsmentioning
confidence: 99%